Gene expression studies of the soybean-nematode interac tion (The Journal of Plant Protection Sciences, 2023)
Soybeans [Glycine max L. (Merr.)] are a ma jor source of protein for animal feed and are  also an increasingly important component of  the diets of consumers. Soybean cyst nema tode (SCN), Heterodera glycines, is the major  pest of soybean and over the last decade ac counted for more than 50% of the crop lost to  disease. Due to improved crop management  and breeding, the loss to SCN decreased to  some extent, but it has been remained a great  challenge. Therefore, further improvement to  control nematode infection is indispensable to  reduce the crop losses. Root-knot nematode  (RKN, Meloidogyne incognita) is also a  pathogen of soybean. Although RKN does  not cause as great a loss to the soybean crop  as SCN, RKN has a very broad host range and  is particularly damaging where soybean is ro tated in with other susceptible crops (1).  Comparison of the pathogenicity of the cyst  and root-knot nematodes is also needed to  create strategies to broaden resistance to  nematodes in soybean and other crops.
Keywords: susceptible; multinucleated; Heterodera glycines